Efeito da temporada sobre a percepcao da síndrome de burnout por atletas de futebol profissional - Bemfica, T. E. B.; Fagundes, L. H. S.; Pires, D. A.; da Costa, V. T. (Revista Brasileira de Ciência e Movimento, 2013)
The burnout syndrome in sports is associated with chronic stress and overtraining that can lead the athlete to be discouraged with the sport and even to the closure of his/her career. However, little is known about the syndrome perceptions in Brazilian professional soccer players. Thus, the present study aimed to evaluate rates of burnout and its dimensions, physical and emotional exhaustion, sport devaluation, and reduced sense of accomplishment sports in professional soccer players and to compare the perceptions of the syndrome in two moments of competitive season: start and end of the Brazilian Championship Series B. Participants were 20 soccer players with a mean age of 24.40 ± 4.55 years belonging to a top level club. It was used the Portuguese version of the Athlete Burnout Questionnaire (QBA) in two moments: first in the round 2 and after in the round 34 of the competition. Data analysis was processed due descriptive statistics and Mann Whitney test. Results showed scores indicative of feelings associated to the syndrome ranged from almost never to rarely in both times, representing a range between 1 and 2 on a 5-point Likert scale. When moments 1 and 2 were compared, no significant differences were observed for total burnout and its dimensions. It can be concluded that this group of athletes showed stable frequency of burnout feelings at the beginning and at the end of the competition, and thus the effect of the season analyzed from two moments did not influence perceptions of burnout and its dimensions.